The effects of caulerpa racemosa composition on the properties of corn starch biodegradable film / Wahida Abdul Rahman, Nur Badiah Raja Roslan and Noor Aishatun Majid - Abdul Rahman, Wahida; Raja Roslan, Nur Badiah; Majid, Noor Aishatun (Universiti Teknologi MARA (UiTM), 2022)
Biodegradable films derived from Caulerpa Racemosa (CR) seaweed and cornstarch were successfully developed via the solution casting method. The effect of CR composition on the properties of cornstarch biodegradable films has been successfully evaluated. FTIR analysis confirmed the existence of good compatibility between CR as a filler and starch as the matrix. The solubility and moisture uptake test revealed a slightly increasing trend when the composition of CR is more than 2.5 %. When the composition of CR increases, the hydrophilicity behaviour of the films increases due to a large number of hydroxyl groups (-OH) that improve its binding water capability. Mechanical test results revealed that increasing CR composition increases the flexibility and elasticity of the films produced. Films with 2.5 % CR exhibit the highest tensile strength and Young's modulus compared to other films. Apart from that, the soil burial test revealed that increasing CR compositions increases the weight loss of the film. Among the overall biodegradable blended films produced, a film with 2.5 % CR composition has been chosen as the best due to its good physical, mechanical, and biodegradability properties. Therefore, different compositions of seaweed and starch can be used to customize a film with the desired application.